Impact of Stress and Depression on the Mental Health of in-school Adolescents’ in Ondo State, Nigeria - Olubunmi , Ojewola, Florence; AKINDUYO, TOSIN EMMANUEL; Idowu, Makinwa, Victoria; Mabaso, N.P.M. (IJBLE Scientific Publications Community Inc., 2024)
This study therefore investigated the impact of stress and depression on the mental health of in-school adolescents in Ondo State. Nigeria. A total of 400 in-school adolescents were selected from public secondary schools using a multistage sampling technique. A self-designed questionnaire titled Assessment of the Impact of Stress and Depression on Mental Health of in-school Adolescents Scale (AISDMHAS) was used to elicit information from the respondents. The data collected were analyzed using descriptive and inferential statistics. The result showed that the adolescents had moderate levels of stress and depression which affected their mental health. There was a relationship between stress, depression, and mental health of the in-school adolescents. Based on the findings, it was recommended that school counselors and non-governmental organizations should organize seminars and programs to create adequate awareness on the issue of stress, and depression as it affect the mental health of adolescents.